KEMAMPUAN GURU KELAS DALAM MENGAJAR ANAK BERKEBUTUHAN KHUSUS BERKESULITAN BELAJAR PADA PROGRAM INKLUSI - Rahayuni, Widias (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Nowadays, the government with its policy of inclusion class made teacher must be able to do learning activity for children with special need. This research was aimed to describe about (1) teachers’ competence in planning of learning for children with special need (CSN), (2) teachers’ competence in doing learning activity for CSN, (3) teachers’ competence in evaluating learning achievement of CSN, (4) teachers’ competence in managing the class at integration process for CSN and normal children in the same class. This research method used descriptive qualitative approach. These research objects were integration class teacher of class 1, class teacher of CSN handler, headmaster of SD Negeri 1 Tanjung. The technique of collecting data in this research used observation, interview, and document. The technique of data analysis used descriptive qualitative. The research result showed that (1)teachers’ competence in the planning of learning for children with special need (CSN) showed two different results between teacher of integration class and teacher of CSN handler, that was in preparing the lesson plan, teacher of the integration class used provided lesson plan and this was applied both to normal student and CSN, yet teacher of CSN prepared batter and conicallu by making PPI for CSN in SD Negeri 1 Tanjung, (2) teachers’ competence in doing learning activity for CSN was in quite a good category as equalized the right if giving learning service between normal student and CSN, and teacher mostly used media in teaching learning process, (3) teachers’ competence in evaluating learning achievement of CSN was based on the competence of CSN, thus teachers didn’t have specific criteria as the standard for determining the development of CSN (4 )teachers’ competence in managing the integration class was able to manage and there was good cooperation between teacher of integration class and teacher of CSN, thus this was good cooperation between teacher of integration class and teacher of CSN, thus this was able to solve the problems in teaching learning process.